Agrobacterium tumefaciens-Mediated Transformation of Pseudocercospora fijiensis to Determine the Role of PfHog1 in Osmotic Stress Regulation and Virulence Modulation - Onyilo, Francis; Tusiime, Geoffrey; Chen, Li-Hung; Falk, Bryce; Stergiopoulos, Ioannis; Tripathi, Jaindra N.; Tushemereirwe, Wilberforce; Kubiriba, Jerome; Changa, Charles; Tripathi, Leena (Frontiers in Microbiology, 2017)
Black Sigatoka disease, caused by Pseudocercospora fijiensis is a serious constraint to banana production worldwide. The disease continues to spread in new ecological niches and there is an urgent need to develop strategies for its control. The high osmolarity glycerol (HOG) pathway in Saccharomyces cerevisiae is well known to respond to changes in external osmolarity. HOG pathway activation leads to phosphorylation, activation and nuclear transduction of the HOG1 mitogen-activated protein kinases (MAPKs). The activated HOG1 triggers several responses to osmotic stress, including up or down regulation of different genes, regulation of protein translation, adjustments to cell cycle progression and synthesis of osmolyte glycerol. This study investigated the role of the MAPK-encoding PfHog1 gene on osmotic stress adaptation and virulence of P. fijiensis. RNA interference-mediated gene silencing of PfHog1 significantly suppressed growth of P. fijiensis on potato dextrose agar media supplemented with 1M NaCl, indicating that PfHog1 regulates osmotic stress. In addition, virulence of the PfHog1-silenced mutants of P. fijiensis on banana was significantly reduced, as observed from the low rates of necrosis and disease development on the infected leaves. Staining with lacto phenol cotton blue further confirmed the impaired mycelial growth of the PfHog1 in the infected leaf tissues, which was further confirmed with quantification of the fungal biomass using absolute- quantitative PCR. Collectively, these findings demonstrate that PfHog1 plays a critical role in osmotic stress regulation and virulence of P. fijiensis on its host banana. Thus, PfHog1 could be an interesting target for the control of black Sigatoka disease in banana.